RELATIONSHIP BETWEEN THE USE OF THE KIA (Children's Health Handbook) AND PREGNANT WOMEN'S KNOWLEDGE IN PREPARATIONFOR CHILDLIFE - Dewi Murtiningsih; Satiyem (Lppm Unan, 2026)
Background: The KIA (Children's Health Handbook) serves as an educational tool designed to increase pregnant women's knowledge about pregnancy, the birth process, and newborn care. However, the level of utilization of the KIA Handbook among pregnant women varies, which impacts their level of understanding of childbirth preparation. This lack of knowledge can affect maternal readiness for childbirth and potentially increase the risk of complications. This study aims to examine the relationship between the use of the KIA Handbook and the level of knowledge of pregnant women in preparing for childbirth. Methods: The research approach used was quantitative with a cross-sectional design. Respondents consisted of pregnant women selected through a purposive sampling technique. Data were collected using a structured questionnaire that assessed the utilization of the KIA Handbook and the knowledge of pregnant women. Data analysis was performed using a chi-square test to determine the relationship between the two variables. Results: The study found that of the 30 respondents, 80% of the respondents utilized the KIA Handbook effectively, with 66.7% having good knowledge and 12.3% having adequate knowledge. 20% of the respondents utilized the KIA Handbook poorly, with 6.7% having good knowledge and 12.3% having adequate knowledge. The chi-square test yielded a p-value <0.013, indicating a relationship between the utilization of the KIA Handbook and pregnant women's knowledge of childbirth preparation. Conclusion: There is a significant relationship between the utilization of the KIA Handbook and pregnant women's knowledge of childbirth preparation. Therefore, health workers need to encourage pregnant women and their families to read, understand, and utilize the KIA Handbook to improve their knowledge and serve as a guide throughout pregnancy and childbirth..